Single maximal versus combination punch kinematics - Piorkowski, B. A.; Lees, A.; Barton, G. J. (Sports Biomechanics, 2011)
The aim of this study was to determine the influence of punch type (Jab, Cross, Lead Hook and Reverse Hook) and punch modality (Single maximal, 'In-synch' and 'Out of synch' combination) on punch speed and delivery time. Ten competition-standard volunteers performed punches with markers placed on their anatomical landmarks for 3D motion capture with an eight-camera optoelectronic system. Speed and duration between key moments were computed. There were significant differences in contact speed between punch types (F2,18,84.87 = 105.76, p = 0.001) with Lead and Reverse Hooks developing greater speed than Jab and Cross. There were significant differences in contact speed between punch modalities (F2,64,102.87 = 23.52, p = 0.001) with the Single maximal (M ± SD: 9.26 ± 2.09 m/s) higher than 'Out of synch' (7.49 ± 2.32 m/s), 'In-synch' left (8.01 ± 2.35 m/s) or right lead (7.97 ± 2.53 m/s). Delivery times were significantly lower for Jab and Cross than Hook. Times were significantly lower 'In-synch' than a Single maximal or 'Out of synch' combination mode. It is concluded that a defender may have more evasion-time than previously reported. This research could be of use to performers and coaches when considering training preparations.